DETERMINAN KEPATUHAN PERAWAT DALAM PENERAPAN KEWASPADAAN STANDAR DI RUMAH SAKIT UMUM DI KOTA DENPASAR TAHUN 2020 - Pradnyana, I Gusti Agung Ngurah Arya; Muliawan, Partha (ARCHIVE OF COMMUNITY HEALTH; Vol 8 No 1 (2021): April 2021DO - 10.24843/ACH.2021.v08.i01.p04, 2021)
ABSTRACT                             Standard Precautios are the minimum infection prevention practices that apply to all patient care, regardless of suspected or confirmed infection status of the patient, in any setting where healthcare is delivered. The aim of this research is to determine the factors associated with compliance to standard precaution among nurses in Pub l ic Hospital Denpasar City. The research design is descriptive-analytical with quantitative method based cross-sectional study. Sample of this research are 76 from 260 nurses in Public Hospital Denpasar City that selected based on systematic random sampling. This research has been conducted during April 2020. The instrument of collecting data use questionnarie and obervations sheets. Data is analyzed in univariable, bivariable, and multivariable. The result of this study showed that the proportion of nurses compliance with standard precaution was 59,21%. The research also showed that variable knowledge, safety climate , , facilities availability, information and training positively correlated with standard precautions compliance (p<0,05) . Multivariable analysis showed that the variable facilities availability is the variable most closely associated with the application of standard precautions. To improve compliance, nurses expose protection of infectious disease should be a priority program through fulfill the needs for the availability of facilities that related to the application of standard precautions compliance. Key Words: Compliance, Standard Precautions, Infectious Diseases, Nurses, Hospital